Export subsidies and countervailing duties under asymmetric information - Matloob Piracha (University of Kent, Department of Economics, 2004)
This paper explores the role of information in the formulation of trade policy for home and foreign country, in a setting in which the home government chooses its subsidy level first after which the foreign firm retaliates by imposing tariffs on its imports. We consider an environment in which home firm costs are private information but it can signal these costs to both policymakers and the foreign firm by choosing the appropriate output level. We show that a low-cost home firm has an incentive to misrepresent itself as high-cost. This is understood by the foreign firm and both policymakers and results in the home government setting a higher subsidy in the signalling case compared to the case when the home firm's output was not a signal of its costs; the foreign government sets the same tariff in both cases.
Keywords: D82; F12; F13; 330; Export subsidy; Tariffs; Incomplete information; Signalling; Exportsubvention; Antidumping; Asymmetrische Information; Signalling